Educating Innovation Managers - The More Things Change, the More They Stay the Same - Fortino, Andres (Senate Hall Academic Publishing, 2007)
When a well respected faculty colleague retired recently he bequeathed to me a book by James Bright, a Harvard Business School professor. The title made me curious: Research, Development and Technological Innovation, and the date was intriguing: 1964. I was surprised (perhaps I should not have been) to see that the very issues we grapple with today in managing innovation have been with us since the dawn of the electronic age. The wonder was that the formulation of the problems and the ways to go about solving them were essentially the same as that tackled by Maital and Ettlie in their more recent books. Although technology is constantly changing, the issues and the underlying principles for managing it do not seem to. I would not be surprised if the prototypical innovator in the Western tradition, Odysseus himself, struggled with these same issues as he went about inventing in the dawn of history.